Uncovering Preservice Teachers' Conceptions of Achievement and Accountability: Evidence from a Framed Field Experiment. (2nd January 2023) - Jennings, Austin S.
ABSTRACT: Contemporary research on preservice teachers' data use opportunities, coursework, and interventions typically focuses on preservice teachers' perceptions about data use comfort, confidence, and preparedness. Despite the contribution of such research to understanding the efficacy of approaches to teacher preparation, understanding preservice teachers' underlying conceptions about data and data use is critical to responsive teacher preparation. However, these conceptions are elusive as preservice teachers do not routinely engage in authentic data use practices. In the present study, I develop a novel methodological approach for uncovering preservice teachers' conceptions about data. Then, I use this framework to investigate how achievement classifications and accountability pressure manifest in preservice teachers' instructional decision-making. Findings suggest preservice teachers have a general propensity for differentially allocating instructional resources to their lowest achieving students and respond to accountability pressure by shifting these resources toward students approaching proficiency criterion and those closest to achievement thresholds. Findings have implications for how teacher preparation programs may leverage preservice teachers' conceptions as a foundation for the development of data literacy, iterative instructional improvement, professional inquiry, and accountable leadership.